1994
DOI: 10.1105/tpc.6.10.1485
|View full text |Cite
|
Sign up to set email alerts
|

Two divergent endo-beta-1,4-glucanase genes exhibit overlapping expression in ripening fruit and abscising flowers.

Abstract: Two structurally divergent endo-beta-1,4-glucanase (EGase) cDNAs were cloned from tomato. Although both cDNAs (Cel1 and Cel2) encode potentially glycosylated, basic proteins of 51 to 53 kD and possess multiple amino acid domains conserved in both plant and microbial EGases, Cel1 and Cel2 exhibit only 50% amino acid identity at the overall sequence level. Amino acid sequence comparisons to other plant EGases indicate that tomato Cel1 is most similar to bean abscission zone EGase (68%), whereas Cel2 exhibits gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(129 citation statements)
references
References 39 publications
7
120
1
1
Order By: Relevance
“…After initiation of abscission, transcripts of abscission-related genes, such as genes for cell wall hydrolysis enzymes and remodeling proteins (for example, PG, Cel, XTH and EXP), commonly show striking increases in different abscised organs (Belfield et al 2005;Cai and Lashbrook 2008;Kalaitzis et al 1997;Lashbrook and Cai 2008;Lashbrook et al 1994;Meir et al 2010;Tucker et al 2007). Simultaneously, cell death is observed in tomato leaf and pedicel abscission and LX ribonuclease is up-regulated (Bar-Dror et al 2011 Chen et al 2011;Fang and Fernandez 2002;Wei et al 2010).…”
Section: Floral Organ Abscissionmentioning
confidence: 99%
“…After initiation of abscission, transcripts of abscission-related genes, such as genes for cell wall hydrolysis enzymes and remodeling proteins (for example, PG, Cel, XTH and EXP), commonly show striking increases in different abscised organs (Belfield et al 2005;Cai and Lashbrook 2008;Kalaitzis et al 1997;Lashbrook and Cai 2008;Lashbrook et al 1994;Meir et al 2010;Tucker et al 2007). Simultaneously, cell death is observed in tomato leaf and pedicel abscission and LX ribonuclease is up-regulated (Bar-Dror et al 2011 Chen et al 2011;Fang and Fernandez 2002;Wei et al 2010).…”
Section: Floral Organ Abscissionmentioning
confidence: 99%
“…Although both Cell and Ce12 mRNA are present in abscission zones and in ripening fruit, Cell mRNA is more abundant than Ce12 mRNA in abscission zones, whereas Ce12 mRNA is most abundant in ripening fruit. Lashbrook et al (1994) demonstrated that both RNAs increase in the abscission zone of tomato flower explants concomitantly with abscission; however, the induction of Cell mRNA was not observed during abscission in planta (de1 Campillo and Bennett, 1996). Two additional members of the EGase family, Ce15 and Ce16, have also been identified in abscission zones, with Ce15 being regulated in the latest stages of abscission (de1 Campillo and Bennett, 1996).…”
mentioning
confidence: 99%
“…EGases are encoded by a large, multigene family, which in tomato consists of at least eight members. Furthermore, endoglucanases are involved in disassembly of a cell wall (Lashbrook et al 1994), but also in the biosynthesis (Mølhøj et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes belong to glycosyl hydrolase family 9 (Henrissat 1991) and their substrates probably include xyloglucan, integral and peripheral regions of non-crystalline cellulose and possibly glucomannan (Brummell and Harpster 2001). EGases have been shown to be expressed during fruit ripening, senescence, in elongating and expanding cells, which suggests a role in plant development (Lashbrook et al 1994;del Campillo and Bennett 1996;Catala et al 1997;Catala et al 2000).…”
Section: Introductionmentioning
confidence: 99%